Leadership, Policy Making, Quality of Economic Policies, and Their Inclusiveness : The Case of Rwanda - Thomas, Rusuhuzwa Kigabo (World Bank, Washington, DC, 2017)
This paper analyzes the role of the leadership in the economic growth in Rwanda, a country that was seriously affected by civil war and the 1994 genocide. It appears that the will and the clear vision of the leadership in Rwanda were one of the central pillars of the very good economic and social performances in Rwanda. This is particularly important because the country has almost no natural resources and the economy and its fundamentals were completely destroyed by the 1994 genocide. This paper thus helps enrich the various economic growth models by stressing the importance of the quality of leadership.